Case Report: Extrinsic Compression of the Left Main Coronary Artery by a Giant Sinus of Valsalva Aneurysm - Ning, Feifei; Tang, Manyun; Wang, Mengjie; Muhlestein, Joseph B.; Day, John D.; Li, Guoliang; Yan, Yang (Frontiers in Cardiovascular Medicine, 2021)
Sinus of Valsalva aneurysm (SoVA) is an uncommon clinical entity, which is present in roughly 0. 09% of the general population. The cause can either be acquired or congenital. Clinically the SoVA of unruptured status are rarely captured or even diagnosed due to atypical clinical presentations. Here, we present a rare case of exertional angina pectoris and recurrent syncope due to an extrinsically compressed left coronary artery by a giant SoVA in a 50-year-old female patient. This SoVA was successfully repaired by the surgical exclusion and the patient was still doing well after 2 years of follow-up.